Dolichopodidae of riverbeds and springs in Croatia with an updated checklist of Croatia (Diptera) - Pollet, Marc; Ivković, Marija (Zootaxa, 2018)
Several invertebrate surveys in Croatia conducted between 2005 and 2014 and including; e.g., Plitvice Lakes, produced 123 bycatch samples of Dolichopodidae (Diptera) from 68 sampling sites collected at 36 localities in seven counties. Seventy-seven were retrieved from emergence traps, six from pan traps and 40 were collected with sweep net and/or aspirator. They contained 420 dolichopodid flies that belonged to 64 species in 22 genera. Four species, Campsicnemus umbripennis, Hercostomus chetifer, Liancalus virens and Syntormon pallipes, accounted for over half of the yields. Contrary to most species that were found in largest numbers in rivers, and their beds in particular, S. pallipes and Hercostomus gracilis were considerably more abundant at springs. Fifty-five species could be added to the national checklist which raises the total number to 94 species. All species records are given, the habitat of each species is described, if possible, and taxonomic notes are provided for some dubious species. Finally, elements are presented to support the assumption that the extant dolichopodid species richness of Croatia is at least three- to fourfold of the current number.